STARTUP SUSTAINABILITY BASED ON GOVERNMENT, TECHNOLOGY, AND MARKET: EMPIRICAL STUDY MEDIATION OF PERFORMANCE & SATISFACTION - Shivhare, Shivani; ., Nupur; Shunmugasundaram, V (Indian Journal of Finance and Banking, 2023)
Start-ups are one of the driving forces of growth and development for developed economies, although emerging economies are now striving to encourage start-ups for the advancement of the country with the support of the startup ecosystem. However, 90 percent of the start-ups failed within a year of their establishment. This study focuses on the factor affecting the sustainability of start-ups, and it is based on primary data collected from 384 start-ups in India. This empirical study analyzed, whether factors such as government support, market orientation, and technology orientation, affected the sustainability of the start-ups by using entrepreneurial satisfaction and performance of the start-ups as the mediators. Correspondingly, the study analyzes the mediation effect of entrepreneurial satisfaction between performance and startup sustainability. The results conveyed that government support, and technology affected startup business sustainability by fostering startup enterprise performance and entrepreneurial satisfaction, while market orientation does not mediate business sustainability using startup enterprise performance as the mediator, and technology orientation affected startup business sustainability with entrepreneurial satisfaction as the mediator.JEL Classification Codes: E20.